Оцінка якості життя хворих після ішемічного інсульту з дисциркуляторною енцефалопатією та артеріальною гіпертензією = Quality of life of the patients with chronic cerebrovascular insufficiency and high blood pressure after the stroke - Ovodiuk, N.; Ovodiuk, M. (Journal of Education, Health and Sport, 2016)
Ovodiuk N., Ovodiuk M. Оцінка якості життя хворих після ішемічного інсульту з дисциркуляторною енцефалопатією та артеріальною гіпертензією = Quality of life of the patients with chronic cerebrovascular insufficiency and high blood pressure after the stroke Journal of Education, Health and Sport. 2016;6(10):601-615. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.189363 http://ojs.ukw.edu.pl/index.php/johs/article/view/4026 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. Оцінка якості життя хворих після ішемічного інсульту з дисциркуляторною енцефалопатією та артеріальною гіпертензією Н. М. Оводюк, М. О. Оводюк Державна наукова установа «Науково-практичний центр профілактичної та клінічної медицини» Державного управління справами, м. Київ, Україна Резюме У статті проведено аналіз дослідження оцінки перебігу дисциркуляторної енцефалопатії ІІ ступеню у хворих (державних службовців), що перенесли ішемічний інсульт на тлі артеріальної гіпертензії в порівнянні з хворими з аналогічним ступенем дисциркуляторної енцефалопатії без перенесеної гострої ішемічної події також на тлі артеріальної гіпертензії. При клінічному та параклінічних дослідженнях було встановлено, що в обох групах мали місце рухові, когнітивні та психічно-вольові розлади. Але у хворих, що перенесли ішемічний інсульт, вищевказані розлади були достовірно більш вираженими, ніж у хворих контрольної групи. Також було доведено, що хворі навіть з малим неврологічним дефіцитом мають достовірно нижчу якість життя. Ключові слова: ішемічний інсульт, дисциркуляторна енцефалопатія, якість життя, артеріальна гіпертензія Quality of life of the patients with chronic cerebrovascular insufficiency and high blood pressure after the stroke N. Ovodiuk, M. Ovodiuk Clinic of State Scientific Institution “Science-Practical Center of prophylactic and clinical medicine” of State Management of Affairs, 5, Verkhnya, Kyiv, 01014, Ukraine Abstract The article presents the study of the chronic cerebrovascular insufficiency combined with high blood pressure in patients (civil servants) who recovered from ischemic stroke in comparison with patients who have chronic cerebrovascular insufficiency with high blood pressure but without ischemic stroke in anamnesis. Due to clinical and paraclinical examinations motor, cognitive, mental and volitional disorders were found in both groups. In the group of patients who have ischemic stroke in anamnesis mentioned disorders were more severe. Also it was proved that patients even with slight neurological impairment have authentically lower quality of life. Key words: ischemic stroke, chronic cerebrovascular insufficiency, high blood pressure, quality of life